Isolation, Purification, Structural Characterization, and in Vitro Lipid-lowering Activity of Evodia rutaecarpa Polysaccharides - Yongjin SUN; Huimei ZENG; Jing HUANG; Yunlong ZHAO; Jinyuan CAI; Song SUN (Shipin gongye ke-ji)
To explore the structural characteristics of Evodia rutaecarpa polysaccharide and its lipid-lowering potential in vitro, Evodia rutaecarpa crude polysaccharide (WPER) was extracted by microwave-assisted extraction technique. Three fractions of WPER, including WPER-1b, WPER-2a and WPER-3a, were isolated and purified by DEAE-52 cellulose ion column and Sepharose G-100 gel column. The physicochemical properties, structure and lipid-lowering activity of the three fractions were characterized. Physicochemical properties showed that the three fractions were mainly composed of Man, Gal and Ara. The total sugar content and uronic acid content of WPER-2a were the highest, which were 66.44%±0.64% and 32.41%±0.99%, respectively. Congo red assay showed that WPER-2a and WPER-3a had a triple helix structure. XRD analysis showed that all the three polysaccharides existed in an amorphous crystalline state. TGA and Zeta potential showed that WPER-2a was more stable than the other two polysaccharides. SEM showed that WPER-1b and WPER-3a were bulk and lamellar, while WPER-2a showed a rough, porous, fragmented shape. The results of the lipid-lowering activity in vitro study showed that the highest lipid adsorption capacity of WPER-3a was 22.96 mg/g at a concentration of 10 mg/mL. When the concentration of WPER-1b, WPER-2a and WPER-3a was 10 mg/mL, the inhibition rates of pancreatic lipase were 65%, 62.33% and 64.31%, respectively. WPER-2a (10 mg/mL) had the better adsorption effect on cholic acid and taurocholate, which were 75.89% and 72.29%, respectively. All the isolated and purified polysaccharides of Evodia officinalis had certain lipid-lowering activity in vitro, and the WPER-2a fraction had the better activity. The results provide reference for improving the development and utilization level of Evodia officinalis polysaccharide, and provide theoretical basis and reference for the application of Evodia officinalis polysaccharide in lipid lowering.